2016
DOI: 10.18553/jmcp.2016.22.8.991
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Economic Impact of Adding Panobinostat to a U.S. Formulary for Relapsed and/or Refractory Multiple Myeloma: A Budget Impact and Cost-Benefit Model

Abstract: Funding for this study was sponsored by Novartis, East Hanover, New Jersey. Bloudek and Kish are employees of Xcenda, a consulting company contracted by Novartis to conduct this analysis. Roy, Globe, and Kuriakose are employees of Novartis. Siegel is on the advisory boards and speaker's bureau of Celgene, Onyx/Amgen, Millennium/Takeda, and Novartis and is on the advisory boards of Merck. Jagannath is a consultant to Sanofi, Bristol-Meyers Squibb, and Celgene. Orloski is a contractor to Xcenda and provided medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…However, DSAs showed that the model results were relatively insensitive to changes in AE rates. Thus, including costs similar to those considered by Bloudek et al 20,23 are unlikely to have changed the results.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, DSAs showed that the model results were relatively insensitive to changes in AE rates. Thus, including costs similar to those considered by Bloudek et al 20,23 are unlikely to have changed the results.…”
Section: Discussionmentioning
confidence: 76%
“…The model methodology used in this case was appropriate for making a comparison across treatments not included in the same trial, which was not necessary in the model by Borg et al 22 One other study has estimated the cost of RRMM therapy in the US. In the analysis by Bloudek et al, 20,23 the estimated monthly total costs (Medicare perspective, including drug costs, administration, and grade 3 or 4 AE prophylaxis and management) per patient treated with POM-d and CAR were $14,733 and $13,438, respectively. Inspection of the cost per treatment year reported by Bloudek et al, 20,23 shows that differences from estimates of this model ($11,966 and $12,489, respectively) were mostly due to the additional AE costs considered ($2,171/mo with POM-d and $1,303/mo with CAR versus $83/mo with POMd and $122/mo with CAR in this model).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is essential even if the innovative services are outsourced to social entrepreneurs on the local health market, according to the planned sustainability approach. The current literature proposes several frameworks for budget impact analysis to provide a comprehensive economic assessment of health care interventions, which can be used by those who manage and set health care budgets, such as the administrators of national and/or regional PHCSs . However, sustainability is not only a financial issue but something more complex and policy makers have to involve all relevant stakeholders and consider the context in which the innovative approach is introduced.…”
Section: Discussionmentioning
confidence: 99%